Leadership challenges in SMEs as a result of remote work due to COVID-19 - Efstathiou, Archontis; Kopsidas, Odysseas; Maska, Laura (Edelweiss Applied Science and Technology, 2024)
Soon after the rapid spread of COVID-19, most of the organizations started to seriously consider the possibilities offered by remote working (teleworking/working from home). The leadership tries to get the best out of the employees through continuous support. The positive aspects of telecommuting have been (among others) the improvement of work productivity, the reduction of overhead costs and the reduction of commuting time and movement and the increase of the possibility of work/life balance. As the number of organizations and employees who have adopted telecommuting continues to grow, the benefits are beginning to show, both in organizations and in the personal lives of employees. This paper investigates employee satisfaction with telecommuting, in the Greek working context, through the collection of primary data and their statistical processing.